Compare students from Univeersity of Brasília by Gender Using t-SNE Techniques - Hansen, Luiza; Borges, Vinicius R.P.; Araujo, Aleteia; Holanda, Maristela (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na Educação, 2019)
The presence of women in technology-related courses is declining every year, reaching in 2016 less than 20% of the total student body in the field of Computer Science in Brazil. This paper proposes to study visualization techniques to analyze and identify profile patterns of undergraduate students on courses in the computing field, comparing gender data (female and male). A visual data and a quantitative analysis were used with dimension reduction technique (t-SNE) considering the students situation at University of Brasília (active, drop out, graduated, death and others). The layouts revealed that the high number of students leaving without graduating is not a gender-related problem. Also the quantitative analysis shows that being in the group of quota students does not have a significant bearing on whether students leave with or without graduating.